Nonnegative polynomial optimization over unit spheres and convex programming relaxations - Zhou, Guanglu; Caccetta, Louis; Teo, Kok Lay; Wu, S. (Society for Industrial and Applied Mathematics, 2012)
We consider approximation algorithms for nonnegative polynomial optimization over unit spheres. Such optimization models have wide applications, e.g., in signal and image processing, high order statistics, and computer vision. Since polynomial functions are nonconvex, the problems under consideration are all NP-hard. In this paper, based on convex polynomial optimization relaxations, we propose polynomial-time approximation algorithms with new approximation bounds. Numerical results are reported to show the effectiveness of the proposed approximation algorithms.